Biodiversity Databases Techniques, Politics, and Applications - Curry, Gordon B.; Humphries, Chris J. (Taylor & Francis, 2007)
With changes in technology and a renewed effort to catalog the world's biodiversity, huge amounts of data are being generated on biodiversity issues. As response to the call for better information systems to manage the biodiversity crisis, a wide range of solutions are being developed for inventorying, managing, and disseminating taxonomic data. This book brings together a diverse array of authors, expertise, and assessors that discuss technical developments to improve the construction, population, and dissemination of biodiversity information. It is designed to inform students and researchers of biodiversity about the changes and challenges that need to be understood by everyone in this information age.